Analisis Risiko Ergonomi dan Intervensi Manual Material Handling pada Toko Bahan Bangunan: Studi Kasus Pengabdian Masyarakat di UMKM Kulon Progo - Apsari, Ayudyah Eka; Nugraheni, Diyah Dwi; Syifa', Ahmad Zada Hilmi (Jurnal ABDI RAKYAT, 2025)
Work-Related Musculoskeletal Disorders (WMSDs) represent a major occupational health challenge in small, and medium enterprises (SMEs), particularly in manual material handling (MMH) activities performed without mechanical assistance. This community service study aimed to analyze ergonomic risks and implement ergonomic interventions in MMH activities at TB. XX, a building material store in Kulon Progo. The method applied a multidisciplinary approach involving workplace observation, ergonomic risk identification, assessment of musculoskeletal complaints, standardized posture analysis, managerial engagement to ensure organizational commitment, and ergonomic interventions through proper lifting technique training and simple assistive devices. The results indicated that three workers performed MMH involving loads of 3–30 kg for approximately four hours per day and reported musculoskeletal complaints in the neck, shoulders, lower back, and legs. Ergonomic and participatory interventions are expected to reduce WMSD risks and improve occupational safety, comfort, and productivity in SMEs